STRATEGI GURU DALAM PEMBELAJARAN AL-QUR’AN HADIS DI MA ANNUR BULULAWANG MALANG - Siti Lailatul Maknunah; Anwar Sa’dullah; Indhra Musthofa (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
In learning the Qur'an, the term strategy is something that is rarely even encountered, which is often only the term method. However, learning to read the Qur'an, especially as a subject in school, absolutely must apply learning strategies in order to achieve the learning objectives that have been determined. The skill of reading the Qur'an that is applied properly and correctly is also the initial potential for the provision of children in understanding the contents content of the Qur'an. In learning the Qur'an, teachers are not only taught to read the Qur'an, but also learn how to behave well in everyday life, so there is a lot of knowledge taught in Islamic education. This research was conducted at MA Annur precisely in the Bululawang area of Malang. To achieve this goal in this research, the researcher uses qualitative research, with data collection procedures carried out including observation, interviews by conducting oral questions and answers with research sources, and documentation in the form of matters relating to the research raised such as photos, notes, reports, etc.